PERANCANGAN WEBSITE SISTEM INFORMASI PELAYANAN RAWAT JALAN PADA PUSKESMAS BENDA BARU PAMULANG - Linda Fransiska Dewi (2021)
Benda Baru Pamulang Community Health Center in conducting community health center services, administration of patient visits and processing patient data is still manually. Managing data manually has the disadvantage that it takes quite a long time, frequent errors in entering patient data, and also when reporting becomes ineffective because it analyzes patients who need damage or missing. For that we need a system that can overcome the problems needed at the Benda Baru Health Center, then a computerized system was built. The purpose of this study is to make the Benda Baru health center service and administration more effective and efficient when the patient is treated. In addition, the puskesmas are more structured and efficient in making service reports. This information system was built based on the website of service activities on New Objects. The information system uses PHP Native and Adobe DreamEaver to create the system. This research uses MySQL to design basic data. This research uses the Agile Scrum Development system development method because this method can adjust the development or existing changes. So this research is an application website to support services at Benda Baru Public Health Center, Pamulang.